Physical Stability Studies of Semi-Solid Formulations from Natural Compounds Loaded with Chitosan Microspheres - Niuris Acosta; Elisa Sánchez; Laura Calderón; Manuel Cordoba-Diaz; Damián Cordoba-Diaz; Senne Dom; Ángeles Heras (Marine Drugs, 2015)
A chitosan-based hydrophilic system containing an olive leaf extract was designed and its antioxidant capacity was evaluated. Encapsulation of olive leaf extract in chitosan microspheres was carried out by a spray-drying process. The particles obtained with this technique were found to be spherical and had a positive surface charge, which is an indicator of mucoadhesiveness. FTIR and X-ray diffraction results showed that there are not specific interactions of polyphenolic compounds in olive leaf extract with the chitosan matrix. Stability and release studies of chitosan microspheres loaded with olive leaf extract before and after the incorporation into a moisturizer base were performed. The resulting data showed that the developed formulations were stable up to three months. The encapsulation efficiency was around 44% and the release properties of polyphenols from the microspheres were found to be pH dependent. At pH 7.4, polyphenols release was complete after 6 h; whereas the amount of polyphenols released was 40% after the same time at pH 5.5.